EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN KONSEP EKONOMI DI SMA NEGERI 3 BONTANG - Berliana, Difa Agil; Sudarman, Sudarman; Riyadi, Riyo (Faculty of Teacher Training and Education, Mulawarman University, 2023)
This research aims to know to know wheter there are effectiviness and the difference bettween using video based learning media and not using media with conventional learning riviewed from student economic concepts understanding. This research is a quantitative research type of quasi-experimental, research with research subjects namely students of class X A as many as 31 people as experimental class and class X B as many as 32 people as control class. Data collection is done by using the test technique. Based on the results of the descriptive analysis, the average for the experimental class increased by 17,75% while the average value for the control class experienced a slight decrease of 0,82%. Throught the results of hypotesis testing, the sig value is obtained. (2-tailed) t-test for Equality of Means is 0,001 so that the significance value is <0,05, which means that H0 is a rejected or Ha is accepted. So, it can be cloncluded the results research showed that there the difference between video based learning media with conventional learning toward student economic concept understanding.